2019
DOI: 10.3390/polym11081341
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Thermally Stable Daidzein-Based Main-Chain-Type Benzoxazine Resins

Abstract: In recent years, main-chain-type benzoxazine resins have been extensively investigated due to their excellent comprehensive properties for many potential applications. In this work, two new types of main-chain benzoxazine polymers were synthesized from daidzein, aromatic/aliphatic diamine, and paraformaldehyde. Unlike the approaches used synthesizing traditional main-chain-type benzoxazine polymers, the precursors derived from daidzein can undergo a further cross-linking polymerization in addition to the ring-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 35 publications
0
20
0
Order By: Relevance
“…[25] Compared with small molecule benzoxazine which using benzoxazine monomer as the polymerization precursor, the main-chain benzoxazine reduces the suspended chain end units and increases crosslink density, thereby improving their thermal, dielectric and mechanical properties. Han et al [27] synthesized two novel main-chain type benzoxazines from daidzein, aromatic/aliphatic diamine, and paraformaldehyde. Daidzein compound possesses two phenolic hydroxyls and a benzopyrone structure which can improve the thermalmechanical properties of thermosets thereby making it an appropriate phenolic resource.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[25] Compared with small molecule benzoxazine which using benzoxazine monomer as the polymerization precursor, the main-chain benzoxazine reduces the suspended chain end units and increases crosslink density, thereby improving their thermal, dielectric and mechanical properties. Han et al [27] synthesized two novel main-chain type benzoxazines from daidzein, aromatic/aliphatic diamine, and paraformaldehyde. Daidzein compound possesses two phenolic hydroxyls and a benzopyrone structure which can improve the thermalmechanical properties of thermosets thereby making it an appropriate phenolic resource.…”
Section: Methodsmentioning
confidence: 99%
“…On the other hand, design and synthesize benzoxazine group terminated molecules can also be used for improving the toughness or for modification of other kinds of thermoset resins. These benzoxazines can be divided into four categories according to their molecular structures: (1) small molecule benzoxazines, [15,23,24] (2) main chain benzoxazines, [25][26][27][28][29] (3) side chain benzoxazines, [30,31] (4) telechelic benzoxazine. [32][33][34] Scheme 2.…”
Section: Toughening Mechanism Of Polybenzoxazinementioning
confidence: 99%
“…The peak at 940 cm À1 was the characteristic absorption peak of the oxazine ring. 36 The peaks at 1025 cm À1 and 1229 cm À1 were the symmetrical and asymmetrical absorption peaks of C-O-C. 37 These characteristic peaks begin to weaken gradually when the temperature was 140 C (Figure 4(a)). This indicated that the ring-opening reaction of the oxazine ring occurred at temperatures 140 C when -CD-MAH was added.…”
Section: Chemical Structure Of -Cd-mah and The Curing Mechanism Of -Cd/ba-a And -Cd-mah/ba-amentioning
confidence: 99%
“…Many BZs derived from renewable, naturally abundant, bio-based phenols (e.g., resveratrol, bisguaiacol-F, sesamol, diphenolic acid, magnolol, eugenol, daidzein, apigenin, guaiacol, naringenin, coumarin, vanillin, sesamol, cardanol, urushiol, and guaiacol) have been easier to prepare, have displayed superior thermal properties and higher cross-linking densities, and have undergone ROP at lower temperatures when compared with those characteristics of BZ resins derived from petroleum compounds [ 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 ]. For example, apigenin-, naringenin-, and daidzein-based bio-BZs have high glass transition temperatures ( T g , up to 360 °C) because they allow additional crosslinking reactions to occur from the olefinic bonds in their molecular structures, leading to highly cross-linked networks after ROP of their BZ units [ 27 , 28 , 29 ]. In addition, the capability of intramolecular hydrogen bonding in these bio-based phenols leads to lower polymerization temperatures, stable latent catalysts, and improved shelf life of such BZ resins [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…For example, apigenin-, naringenin-, and daidzein-based bio-BZs have high glass transition temperatures ( T g , up to 360 °C) because they allow additional crosslinking reactions to occur from the olefinic bonds in their molecular structures, leading to highly cross-linked networks after ROP of their BZ units [ 27 , 28 , 29 ]. In addition, the capability of intramolecular hydrogen bonding in these bio-based phenols leads to lower polymerization temperatures, stable latent catalysts, and improved shelf life of such BZ resins [ 27 , 29 ].…”
Section: Introductionmentioning
confidence: 99%